Looking for Innovation Opportunity Areas in the Value Chain in the Agri-food Sector - Vega-Salinas, Roberto Isaias; Vega-Gonzalez, Luis Roberto; Garcia-Lira, Alan (Business and Economic Research, 2025)
Agricultural producers know their business very well, through daily practice they know the best way to carry out their processes; however, currently, it is necessary to continually seek improvements in its production processes to remain competitive and not only survive but grow. Thus, today we speak of open innovation, which implies the establishment of networks, made up of diverse local, regional, national and international nodes and components through which small or medium-sized producers can learn about experiences from other latitudes, which help them develop innovation projects to stay competitive. Through the review and analysis of cases of some Mexican agricultural producers and other Latin American countries based on the experience and proposals of some international organizations, which use the network innovation model, in this work a simple and synthetic proposal is developed for the opportunity areas to carry out innovation projects in the different links of the value chain of agri-food production processes.